Primary care doctors retirements in the context of an ageing population in Italy - Dalla Valle, Zeno; Signorelli, Carlo; Renzi, Cristina (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Ongoing shortages in primary care doctors/primary care paediatricians and increasing healthcare needs due to ageing of the population represent a great challenge for healthcare providers, managers, and policymakers. To support planning of primary healthcare resource allocation we analyzed the geographic distribution of primary care doctors/primary care paediatricians across Italian regions, accounting for area-specific number and age of the population. Additionally, we estimated the number of primary care doctors/primary care paediatricians expected to retire over the next 25 years, with a focus on the next five years. Study design. Ecological study. Methods. We gathered the list of Italian general practitioners and primary care paediatricians and combined them with the data from the National Federation of Medical Doctors, Surgeons and Dentists. Using data from the National Institutes of Statistics, we calculated the average number of patients per doctor for each region using the number of residents above and under 14 years of age for general practitioners and primary care paediatricians respectively. We also calculated the number of residents over-65 and over-75 years of age per general practitioner, as elderly patients typically have higher healthcare needs. Results. On average the number of patients per general practitioner was 1,447 (SD: 190), while for paediatricians it was 1,139 (SD: 241), with six regions above the threshold of 1,500 patients per general practitioner and only one region under the threshold of 880 patients per paediatrician. We estimated that on average 2,228 general practitioners and 444 paediatricians are going to retire each year for the next five years, reaching more than 70% among the current workforce for some southern regions. The number of elderly patients per general practitioner varies substantially between regions, with two regions having >15% more patients aged over 65 years compared to the expected number. Conclusions. The study highlighted that some regions do not currently have the required primary care workforce, and the expected retirements and the ageing of the population will exacerbate the pressure on the already over-stretched healthcare services. A response from healthcare administrations and policymakers is urgently required to allow equitable access to quality primary care across the country.